2020
DOI: 10.3390/foods9060818
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Mediated Beany Flavor Masking and Textural Modification of an Isolated Soy Protein-Based Yuba Film

Abstract: The application of β-cyclodextrin (CD) to remove unattractive volatile compounds has been applied in various food products. This study investigated the effect of CD concentration (1–4%) on the beany flavor masking and textural modification of yuba film prepared by isolated soy protein (ISP) in the presence of (+CD), or after removing, the flavor-entrapped CD (−CD). Based on gas chromatography–mass spectrometry (GC–MS), the addition of CD caused a decrease in 1-octen-3-ol, benzaldehyde, hexanal, and 2-heptanone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In some previous studies, the addition of lower CD concentrations to soy-based foods did not affect their sensory attributes [ 15 , 35 ]. It is indicated that these foods contained a quantity of volatile beany flavor compounds, well above their threshold values, compared with the addition amounts of CDs.…”
Section: Resultsmentioning
confidence: 91%
“…In some previous studies, the addition of lower CD concentrations to soy-based foods did not affect their sensory attributes [ 15 , 35 ]. It is indicated that these foods contained a quantity of volatile beany flavor compounds, well above their threshold values, compared with the addition amounts of CDs.…”
Section: Resultsmentioning
confidence: 91%
“…β ‐CD is a kind of cyclic oligosaccharide, which is usually 6–8 glucose residues in length, and the bond type in the middle is 1–4 glycosidic bond (Pinho et al, 2014). Cyclodextrin is characterized by its hydrophilic appearance and hydrophobic inner cavity, so it can be used to wrap hydrophobic molecules (Lee et al, 2020). Nanoencapsulation by β‐cyclodextrin can produce satisfactory sensory properties and produce an optically transparent solution (Katouzian & Jafari, 2016).…”
Section: Flavor Encapsulationmentioning
confidence: 99%
“…16,17 According to reports, ⊎-cyclodextrin decreases the content of 1-octene-3-ol, 2-heptanone benzaldehyde, and hexanal, which effectively reduces the beany flavor of a soy protein-lipid film, and has positive effects on textural characteristics of the film. 18 It is also found that ⊎-CD could effectively capture short-chain free fatty acids, reduce goat milk flavor in soft goat cheese, and enhance product acceptability. 19 Furthermore, ⊎-CD and polymerized whey protein have a synergistic effect on the binding of short-to medium-chain free fatty acids in goat milk, which can effectively improve the sensory properties and textural characteristics of fermented goat milk.…”
Section: Introductionmentioning
confidence: 99%
“…It can capture hydrophobic molecules and remove undesirable flavors from the food system, and is extensively applied in the food industry 16, 17 . According to reports, β‐cyclodextrin decreases the content of 1‐octene‐3‐ol, 2‐heptanone benzaldehyde, and hexanal, which effectively reduces the beany flavor of a soy protein–lipid film, and has positive effects on textural characteristics of the film 18 . It is also found that β‐CD could effectively capture short‐chain free fatty acids, reduce goat milk flavor in soft goat cheese, and enhance product acceptability 19 .…”
Section: Introductionmentioning
confidence: 99%